Status of the neutron time‐of‐flight single‐crystal diffraction data‐processing software STARGazer. Issue 11 (2nd November 2018) - Yano, Naomine; Yamada, Taro; Hosoya, Takaaki; Ohhara, Takashi; Tanaka, Ichiro; Niimura, Nobuo; Kusaka, Katsuhiro
Abstract : In this article, the status of the STARGazer data‐processing software and its data‐processing algorithms are described in detail. The STARGazer data‐processing software is used for neutron time‐of‐flight single‐crystal diffraction data collected using the IBARAKI Biological Crystal Diffractometer. Abstract : The STARGazer data‐processing software is used for neutron time‐of‐flight (TOF) single‐crystal diffraction data collected using the IBARAKI Biological Crystal Diffractometer (iBIX) at the Japan Proton Accelerator Research Complex (J‐PARC). This software creates hkl intensity data from three‐dimensional ( x, y, TOF) diffraction data. STARGazer is composed of a data‐processing component and a data‐visualization component. The former is used to calculate the hkl intensity data. The latter displays the three‐dimensional diffraction data with searched or predicted peak positions and is used to determine and confirm integration regions. STARGazer has been developed to make it easier to use and to obtain more accurate intensity data. For example, a profile‐fitting method for peak integration was developed and the data statistics were improved. STARGazer and its manual, containing installation and data‐processing components, have been prepared and provided to iBIX users. This article describes the status of the STARGazer data‐processing software and its data‐processing algorithms.